Activated H-ras rescues E1A-induced apoptosis and cooperates with E1A to overcome p53-dependent growth arrest. - Lin, H J (1995)
The adenovirus E1A oncogene products stimulate DNA synthesis and cell proliferation but fail to transform primary baby rat kidney (BRK) cells because of the induction of p53-mediated programmed cell death (apoptosis). Overexpression of dominant mutant p53 (to abrogate wild-type p53 function) or introduction of apoptosis inhibitors, such as adenovirus E1B 19K or Bcl-2 oncoproteins, prevents E1A-induced apoptosis and permits transformation of BRK cells. The ability of activated Harvey-ras (H-ras) to cooperate with E1A to transform BRK cells suggests that H-ras is capable of overcoming the E1A-induced, p53-dependent apoptosis. We demonstrate here that activated H-ras was capable of suppressing apoptosis induced by E1A and wild-type p53. However, unlike Bcl-2 and the E1B 19K proteins, which completely block apoptosis but not p53-dependent growth arrest, H-ras expression permitted DNA synthesis and cell proliferation in the presence of high levels of wild-type p53. The mechanism by which H-ras regulates apoptosis and cell cycle progression is thereby strikingly different from that of the E1B 19K and Bcl-2 proteins. BRK cells transformed with H-ras and the temperature sensitive murine mutant p53(val 135), which lack E1A, underwent growth arrest at the permissive temperature for wild-type p53. p53-dependent growth arrest, however, could be relieved by E1A expression. Thus, H-ras alone was insufficient and cooperation of H-ras and E1A was required to override growth suppression by p53. Our data further suggest that two complementary growth signals from E1A plus H-ras can rescue cell death and thus permit transformation.